Perbandingan Food Coping Strategi dan Kejadian Stunting Pada Rumah Tangga Diperdesaan dan Perkotaan : Perbedaan Food Coping Strategy antara Rumah Tangga di Perdesaan dan Perkotaan terhadap Kejadian Stunting - Pujokaroni, Agustu Sholeh; Utoro, Panggulu Ahmad Ramadhani; Aini, Qurratu; Saragih, Bernatal (Amerta Nutrition, 2023)
Background: Stunting is one of the growth and development disorders of children as a consequence of a chronic nutrition deficiency and repeated infection, reflected by the height below the standard. Objectives: This research aims to recognize the differences in food coping strategies between rural and urban households toward stunting incidents. Methods: Cross-sectional design with 300 children in Paser Regency (rural) and Balikpapan City (urban). Assessment of daily nutrition intake of the children using multiple-passed 1 x 24-hour recall to the mother. The household dietary diversity was assessed using the Household Dietary Diversity Score (HDDS). In each household, Anthropometry was measured on the children (weight and height) and mother (weight, height, the middle of the upper arm, waist, and hips). Results: The survey showed that the wife was more dominant in determining the food menu, cost of food, and the processing of nutritious food. Food coping strategies in rural households are to consume less favorable food cheaper, collect wild plants, hunt or harvest early, and ask for food or help from colleagues or siblings; meanwhile, food coping strategies in urban households are to consume less favorable food and cheaper. Food security in urban households was 75.3%, and in rural households was 59.3%. The average infant's body length in rural and urban households was 49.22 cm, and the proportion of short infants was 7.33% in urban households and 14.67% in rural households. Conclusions: The food coping strategy performed in rural households was deeper than in urban households.